Effects of elevated ambient temperature on embryo implantation in rats - Hamid, Huda Yahia; Abu Bakar @ Zakaria, Md Zuki; Yimer, Nurhusien; Goh, Yong Meng; Haron, Abd Wahid; Mohamed Mustapha, Noordin (Academic Journals, 2012)
Implantation is a crucial step in mammalian reproduction as it is a gateway to further embryonic development and successful pregnancy. Changes in the environmental factors, such as temperature have adverse effects on reproduction. However, the impact of elevated temperature on the implantation process is not well defined. The objective of this study was to investigate the possible effect of elevated ambient temperature on implantation time and rate. The results revealed that exposure to elevated ambient temperature leads to a delayed implantation and reduced number of implantation sites in Sprague Dawley rats. Moreover, the exposure to elevated temperature resulted in change in the progesterone and estradiol patterns during the implantation time. These findings indicate that elevated temperature disturbs the implantation process.